Studi Penyusunan Database Infrastruktur Transportasi Perhubungan Darat Kabupaten Kayong Utara - Azwansyah, Heri (Faculty of Engineering, Universitas Tanjungpura, 2013)
Abstract Initial steps to develop transport infrastructure is to conduct an inventory of transportation. This study is an effort to map the existing conditions of transportation in North Kayong districts, especially in the field of land transportation. This study requires data transportation land transportation infrastructure are derived from relevant agencies and field surveys. This study resulted in a database of transport infrastructure in the field of land transportation Kayong northern district can be implemented with web GIS applications. this can provide mapping information of transportation infrastructure land transportation fields scattered throughout the northern district Kayong Keywords Database, Transport Infrastructure